2019
DOI: 10.1002/cbic.201900565
|View full text |Cite
|
Sign up to set email alerts
|

The l‐Alanosine Gene Cluster Encodes a Pathway for Diazeniumdiolate Biosynthesis

Abstract: N‐Nitroso‐containing natural products are bioactive metabolites with antibacterial and anticancer properties. In particular, compounds containing the diazeniumdiolate (N‐nitrosohydroxylamine) group display a wide range of bioactivities ranging from cytotoxicity to metal chelation. Despite the importance of this structural motif, knowledge of its biosynthesis is limited. Herein we describe the discovery of a biosynthetic gene cluster in Streptomyces alanosinicus ATCC 15710 responsible for producing the diazeniu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 32 publications
(29 reference statements)
2
32
1
Order By: Relevance
“…We proposed that 3 would be the initial substrate of the NRPS complex HamD and that the enzymes of unknown functions, HamA and HamE, and the N ‐oxygenase analogue HamC would transform the amine into the diazeniumdiolate. This hypothesis is supported by the previous identification of several modifications occurring during chain elongation and by recent investigations of alanosine biosynthesis . The compound would be released as an aldehyde from the reductase domain of HamD and further reduced through the action of the same enzyme to afford 2 .…”
Section: Methodssupporting
confidence: 53%
See 1 more Smart Citation
“…We proposed that 3 would be the initial substrate of the NRPS complex HamD and that the enzymes of unknown functions, HamA and HamE, and the N ‐oxygenase analogue HamC would transform the amine into the diazeniumdiolate. This hypothesis is supported by the previous identification of several modifications occurring during chain elongation and by recent investigations of alanosine biosynthesis . The compound would be released as an aldehyde from the reductase domain of HamD and further reduced through the action of the same enzyme to afford 2 .…”
Section: Methodssupporting
confidence: 53%
“…Furthermore, preliminary experiments explored the origin of the terminal N atom of the diazeniumdiolate group and chromatographic evidence suggested that it originated from nitrite. Recently, several reports have indicated similar biosynthetic pathways for the diazeniumdiolate alanosine, the diazo compounds cremeomycin and kanamycin, the pyridazine azamerone, the N ‐hydroxytriazenes triacsins and the hydrazide fosfazinomycin …”
Section: Methodsmentioning
confidence: 99%
“…The most frequently used precursors for N-N bond formation are hydroxylamines (such as L-N 5 -OH-Ornthine in piperazate pathway 9 , N-isobutylhydrdoxylamine in valanimycin pathway 37 , and L-N 6 -OH-lysine in the pathways of s56-p1 14 , pyrazomycin 16 and formycin 17,38 ) and nitric acid, which derives from the α-amine of L-aspartic acid by the enzyme pair CreE and CreD 10 . The flavin monooxygenase CreE and nitrosuccinate lyase CreD were first characterized in the cremeomycin pathway, and their homologs were subsequently identified in the pathways of fosfazinomycin, and kinamycin, triacsins and alanosine 15,[21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
“…While the biosynthetic routes to natural products containing a N-N bond have received great interest and are starting to be revealed, how a triazole ring is assembled in nature remains unknown [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . Elucidation of its biosynthetic mechanism could likely be helpful to the design of synthetic biology approaches for producing triazoles.…”
mentioning
confidence: 99%
“…Reaction of the hydroxylamine with a nitrite electrophile could form the diazeniumdiolate N À N bond of valdiazen (Figure 4). This reaction has been proposed for the biosynthesis of fragin [3,16] and alanosine [17] that also contain a diazeniumdiolate. [3,[16][17][18] The nitroso product may also be involved in biosynthesis (Supporting Information, Figure S32), but its role needs further investigation.…”
Section: Angewandte Chemiementioning
confidence: 99%